Molecular characterization and phylogenetic analysis of Fasciola species in sheep and goats in Sulaymaniyah Province, Northern Iraq - Raoof, Hana Sherzad; Marif, Hardi Fattah; Rahman, Heshu Sulaiman; Sheikh, Mohammed Omar Baba; Ahmed, Arkan Manucher San (Sulaimani Journal for Pure and Applied Sciences, 2020)
Both F. hepatica and F. gigantica are considered as the main causes of human and animal fascioliasis that have much medical and economic importance worldwide. Nowadays, identification and description of Fasciola species using molecular-based techniques are critical and reliable approach in most laboratories and research centers. Thus, this research aimed to investigate the prevalence of fascioliasis and molecular characterization of isolated Fasciola species in sheep and goats in Sulaimaniyah province, Northern Iraq. Briefly, a total of 100 liver samples from slaughterhouse and 100 fecal samples from the animal field were collected from sheep and goats. In overall collected liver specimens, only 30 (15%) samples were found to be positive using polymerase chain reaction (PCR) assay, from which only 6 samples were selected for sequencing of the partial mitochondrial 28S rRNA gene and codon analysis. Simultaneously, the collected fecal samples were also analyzed using the Fecal Egg Count Reduction Test (FECRT), in which only 4 samples were positive. The results revealed that the identified four field sequences strains were F. hepatica and the other two field sequences were F. gigantica. In conclusion, we revealed that both F. hepatica and F. gigantica were distributed in Sulaimaniyah province and the mitochondrial 28S rRNA gene is confirmed as a potential biomarker in identifying various Fasciola species
Keywords: Liver fluke; tissue biomarker; small ruminants; abattoir; gene sequencing